Influence of Reservoir Load on a Neighbouring Reverse Fault: A Simulation - Chander, R.; Sarkar, I. (Journal of Nepal Geological Society, 1995)
The simulation of reservoir induced seismicity indicates that a finite reservoir situated on the footwall of a reverse fault can induce a tendency towards instability.